2018
DOI: 10.1016/j.ebiom.2018.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Spread of MCR-3 Colistin Resistance in China: An Epidemiological, Genomic and Mechanistic Study

Abstract: BackgroundMobilized resistance to colistin is evolving rapidly and its global dissemination poses a severe threat to human health and safety. Transferable colistin resistance gene, mcr-3, first identified in Shandong, China, has already been found in several countries in multidrug-resistant human infections. Here we track the spread of mcr-3 within 13 provinces in China and provide a complete characterization of its evolution, structure and function.MethodsA total of 6497 non-duplicate samples were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
98
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(110 citation statements)
references
References 97 publications
(175 reference statements)
9
98
0
3
Order By: Relevance
“…Retrospectively, a similar scenario is seen with the MCR family of polymyxin resistance [12][13][14]. Not only have the new mcr variants already been extended from mcr-1 [1,14,15] to mcr-9 [16,17], but also some of them, like mcr-1 [1,12] and mcr-3 [1,18], have disseminated globally. Thus, it is in great demand to gain insights into the molecular epidemiology of tet(X)-mediated tigecycline resistance.…”
Section: Introductionmentioning
confidence: 74%
“…Retrospectively, a similar scenario is seen with the MCR family of polymyxin resistance [12][13][14]. Not only have the new mcr variants already been extended from mcr-1 [1,14,15] to mcr-9 [16,17], but also some of them, like mcr-1 [1,12] and mcr-3 [1,18], have disseminated globally. Thus, it is in great demand to gain insights into the molecular epidemiology of tet(X)-mediated tigecycline resistance.…”
Section: Introductionmentioning
confidence: 74%
“…The mcr-4 has been identified first in S. enterica isolated from a pig on an 8,749 bp ColE10 plasmid in Italy [77,92]. Sequence analysis showed that mcr-4 has 34.0%, 35.0%, and 49.0% amino acid sequence identity to mcr-1, mcr-2, and mcr-3, respectively.…”
Section: Plasmid-mediated Resistance To Polymyxinsmentioning
confidence: 99%
“…Intriguingly, the determinants of transferable colistin resistance have extended further away mcr-1 to include a number of novel mcr-1 alleles [92]. Up to now, nine mcr alleles have been reported including mcr-1 [75][76][77][78][79]81,82,93], namely; mcr-2 (1617 bp) [79], mcr-3 (1626 bp) [82], mcr-4 (1626 bp) [77], mcr-5 (1644 bp) [76], mcr-6 (1617 bp) [75], mcr-7 (1620 bp) [81], mcr-8 (1698 bp) [78], and the most recently detected mcr-9 (2661 bp) [93] (Table 2).…”
Section: Plasmid-mediated Resistance To Polymyxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Venezuela e 744 SSSI 4 (R) suggest that these genes are prone to mutations as they spread, as was observed in the isolates from Peru. A much higher prevalence of mcr-like genes from specific geographic locations (1,10,11) accompanied by the first report of mcr-1 in Pseudomonas aeruginosa (12) located on a chromosome demonstrate the ability of this gene to disseminate. Continued monitoring of mcr genes is warranted, but the development of global policies that might decrease the use of agents important to treat human infections or agents known to coselect for these resistance genes (13) seems prudent.…”
mentioning
confidence: 99%